PENGARUH PEMBERIAN KOMPRES DAUN KUBIS DINGIN (BRASSICA OLERACEA VAR. CAPITATA) TERHADAP SKALAPEMBENGKAKAN PAYUDARA PADA IBU POSTPARTUM DI WILAYAH KERJA PUSKEMAS KOTABUMI UDIK - Iis Tri Utami; Maya Renzy Meriyanti (Jurnal Maternitas Aisyah (JAMAN AISYAH), 2021)
Breast engorgement is the problem that is often undergo by mothers after the childbirth process. The genesis rate reached 20-80%, 10% of them experience severe pain that requires pharmacological treatment. Breast engorgement is not handled properly will cause mastitis and infection. The treatment that can be done in healing with Breast engorgement is to compress by using cold cabbage leaves. The research type used pre-experiment with one group pretest posttest design. The respondents in this research were postpartum mothers with breast engorgement which 38 respondents were given cold cabbage leaves compress for 3 days which were done twice a day morning and evening. The research instrument used the checklist, it is a direct assessment of the genesis of breast engorgement used the Six Point Engorgement Scale (SPES). In quantitative data analysis used Wilocxon test. The results of univariate showed that the majority of respondents before the intervention had a scale of swelling with a scale of 4 as many as 14 respondents (36.8%) and the majority of respondents after the intervention had a scale of swelling on a scale of 2 were 23 respondents (60.5%) . The results of bivariate analysis obtained the effect of cold cabbage leaves compress on reducing breast engorgement were p-value of 0,000. It can be practiced independently by the patients as an alternative to breast care with non-pharmacological methods.